Associations between the red blood cell distribution width and 30-day mortality in critically ill patients with delirium: a retrospective study using the MIMIC-IV database - Ma, Songmei; Lin, Lin; Zheng, Shuwen; Liu, Zhenjing; Kong, Li; Wang, Haiyun (Frontiers in Aging Neuroscience, 2025)
BackgroundRed blood cell distribution width (RDW) is associated with increased mortality risk in critically ill patients. However, limited data are available on critically ill patients with delirium.MethodsData from the Multiparameter Intelligent Monitoring in Intensive Care Database IV (MIMIC-IV) version 3.1 database were analyzed in this retrospective cohort research. The Confusion Assessment Method for the Intensive Care Unit (CAM-ICU) criteria were used to identify critically ill patients with delirium. The first RDW value was extracted within the first 24 h after intensive care unit admission. The endpoint was 30-day all-cause mortality. Multivariable Cox regression analysis was performed to examine the relationship between RDW and 30-day mortality. Age, sex, myocardial infarction, congestive heart failure, peripheral vascular disease, dementia, cerebrovascular disease, chronic pulmonary disease, diabetes, sepsis, and hemoglobin were considered for subgroup analysis.ResultsA total of 10,600 patients were included, with a mean (standard deviation) age of 67.0 (16.7) years, of whom 6,007 (56.7%) were male patients. The increase in RDW was correlated with an increased risk of 30-day mortality in the Cox proportional regression analysis model (Hazard Ratio [HR] 1.04; 95% confidence interval [CI] 1.03–1.04). In comparison with the low-RDW group, the middle and high-RDW groups tended to have higher risks of 30-day all-cause mortality (HR, 1.54; [95% CI] [1.34–1.77]; HR 2.25 [95% CI] [1.96–2.58]; P trend < 0.0001). Restricted cubic spline (RCS) analysis demonstrated linear relationships between RDW and 30-day mortality. Subgroup analyses using the entire cohort also demonstrated higher 30-day all-cause mortality. Subgroup analyses across the entire cohort confirmed elevated 30-day all-cause mortality associated with higher red cell distribution width (RDW), with results aligning closely with the Cox proportional regression findings.ConclusionAn increase in RDW was associated with an increased risk of 30-day all-cause mortality in critically ill patients with delirium. RDW may serve as a valid indicator for assessing the severity and guiding the treatment of delirium patients in the ICU.